Building Legal Awareness Through Digital Platforms: Conceptualizing Web Applications in Responsive Legal Counseling - Serah, Yenny Aman; Purwanto, Purwanto; Febrianawati, Febrianawati; Sirait, Resmaya Agnesia Mutiara; Astono, Agustinus (Universitas Negeri Semarang, 2025)
The phenomenon of low legal awareness remains a common characteristic of society in Indonesia, particularly in the province of West Kalimantan. This demonstrates the need for new innovations in legal education methods that are relevant to the current digital era. This study aims to conceptualize a web-based legal education model through the development of the SAHABAT (Sobat Hukum Kalimantan Barat) application as a responsive and inclusive digital medium to improve public legal literacy. The research method used a socio-legal approach with a qualitative descriptive method, involving literature studies, in-depth interviews, and field observations on the need for access to legal information. The data used in this study was primary data obtained directly from legal educators at the West Kalimantan Provincial Office of the Ministry of Law and Human Rights. The results of the study show that the community needs an outreach platform that is easily accessible, interactive, and contextual to legal issues. The SAHABAT application is designed to provide popular legal information, online consultations, and topic-based legal education through interactive features. This study confirms that digitizing legal counseling through platforms such as SAHABAT can be a means of helping to increase legal awareness and community participation in realizing a responsive legal culture. This study recommends the integration of the SAHABAT application into the national legal counseling strategy as part of the digital transformation of public services in the legal field.